2013
DOI: 10.1523/jneurosci.2240-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

On the Dissociation between Microsaccade Rate and Direction after Peripheral Cues: Microsaccadic Inhibition Revisited

Abstract: Microsaccades during fixation exhibit distinct time courses of frequency and direction modulations after stimulus onsets, but the mechanisms for these modulations are unresolved. On the one hand, microsaccade rate drops within Ͻ100 ms after stimulus onset, a phenomenon described as microsaccadic inhibition. On the other, the directions of the rare microsaccades that do occur during inhibition are, surprisingly, the most highly correlated with stimulus location. Here we show, using a combined computational and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
225
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(272 citation statements)
references
References 56 publications
47
225
0
Order By: Relevance
“…The superior colliculus is causally involved in generating microsaccades (Hafed et al 2009). One model for oculomotor freezing is that a sensory signal arriving in the superior colliculus suppresses ongoing activity or raises the threshold for saccade execution (Hafed and Ignashchenkova 2013;Rolfs et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The superior colliculus is causally involved in generating microsaccades (Hafed et al 2009). One model for oculomotor freezing is that a sensory signal arriving in the superior colliculus suppresses ongoing activity or raises the threshold for saccade execution (Hafed and Ignashchenkova 2013;Rolfs et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, response enhancement, an attentional signature, can also occur in tight synchrony with individual microsaccades. Starting from this hypothesis, using behavioral and computational studies, we recently found that spatial attentional performance was modulated peri-microsaccadically [19,24]; the largest attentional effects occurred when targets appeared around microsaccades, during a period in which visual perception is altered [24]. Here, we investigated possible neuronal correlates of these findings.…”
Section: Introductionmentioning
confidence: 92%
“…After fixating on a spot for 400-550 ms, the spot transiently dimmed for 50 ms, which reset microsaccadic rhythms [19] without inducing a spatial bias in microsaccades. After 110-320 ms, a vertical sine wave grating (2.22 cycles/ ) appeared for 300 ms within a neuron's response field (RF) (Figure 1A).…”
Section: Response Enhancement For Stimuli Before Microsaccadesmentioning
confidence: 99%
See 2 more Smart Citations